An overview of self-medication: a major cause of antibiotic resistance and a threat to global public health - Mubasher Rehman; Shehzad Ahmed; Umair Ahmed; Kosar Tamanna; Muhammad Shehryar Sabir; Zeeshan Niaz (Journal of the Pakistan Medical Association, 2020)
Self-medication is the use of medicines by people on their own experience without consulting a doctor. People use medicines for pain management or to cure a disease and sometime this may be unnecessary. There are a lot of public and professional health concerns about miss usage of medicines and globally physicians agree upon this rising issue that leads to antibiotic resistance. In developing countries medicines without prescription are easily available which results in many adverse outcomes especially bacterial resistance. Insufficient health care services and socioeconomic factors result in increased proportion of self-medication as compared to drugs prescribed by physicians. This review article is focused on indicating prevalence rate of self-medication in different developed and under developed countries, major risk factors and control of self-medication due to which antibiotic resistance rate can be minimized.